Evaluasi Kebutuhan dan Estimasi Biaya Alat Muat Kobelco 380 dan Hitachi 350 Dengan Alat Angkut Scania P360 dan Mercedez Actroz 4043 Pada Pengupasan Overburden PT. Caritas Energi Indonesia Jobsite KBB, Sarolangun - Eric Sandeir; Heri Prabowo (Journals Mining Engineering : Bina Tambang, 2018)
Based on field observation on overburden removal at PT. Caritas Energi Indonesia, found that the production activity of overburden removal has not been optimal. This caused by the inconsistency between loading and transporting equipment, inefficiency of equipment and match factor which do not match, which is evident from the presence of equipment waiting in the field. The total production of actual loading equipment was 168.653,5 BCM/month, and hauling equipments was 103.530,2 BCM/month, this results in not achieving the planned overburden production target. After the analysis has obtained the cause of low production is due to the low efficiency of work and the lack of hauling equipment used. By increasing work efficiency and adding hauling equipment, total loading equipment is 185.630,4 BCM/month and hauling equipments are 177.781,7 BCM/month. The number of production increases but has not reached production targets due to high rainfall in March, the company spends a lot of time waiting for rain and slippery. This will have an impact on the increase of unavoidable standby time. From the calculation results obtained the amount of production costs of loading and hauling equipments for overburden removal before analyzed is Rp.1.095.056.103,11 /month or Rp.10.577,17/BCM, and after analyzed the amount of production cost become Rp.1.552.132.079,73/ month or Rp.8.730,55/BCM. And based on the calculation of BESR obtained SR economic value is 3,91.Keywords: Overburden, Work Efficiency, Match Factor, Production Cost, BESR.